Gamma/Delta T Cells and Their Role in Protection Against Malaria - Deroost, Katrien; Langhorne, Jean (Frontiers in Immunology, 2018)
Whether and how γδT cells play a protective role in immunity against Plasmodium infection remain open questions. γδT cells expand in patients and mice infected with Plasmodium spp, and cytokine production and cytotoxic responses against blood-stage parasites are observed in vitro. Their expansion is associated with protective immunity induced by irradiated sporozoite immunization, and depletion of γδT cells in some mouse models of malaria excacerbates blood-stage infections. It is now clear that these cells can have many different functions, and data are emerging suggesting that in addition to having direct parasitocidal effects, they can regulate other immune cells during Plasmodium infections. Here we review some of the historic and more recent data on γδT cells, and in light of the new information on their potential protective roles we suggest that it is a good time to re-evaluate their activation requirements, specificity and function during malaria.